Electroluminescence of new coordination compounds of europium ions with β-diketones, acetic and butyric acids - Osadchenko, A.V.; Ambrozevich, S.A.; Zakharchuk, I.A.; Vashchenko, A.A.; Daibagya, D.S.; Ryzhov, A.V.; Pevtsov, D.N.; Pevtsov, N.V.; Selyukov, A.S. (Nauchno-tekhnicheskiĭ vestnik informat͡s︡ionnykh tekhnologiĭ, mekhaniki i optiki, 2024)
In this work, organic light-emitting LEDs based on Eu3+ coordination compounds with β-diketones and acetic and butyric acids were created and studied. At the moment, an active search is underway for new materials to create optoelectronic devices with high luminescent characteristics. One of these characteristics is high color purity and it can be achieved through the use of materials with narrow-band luminescence, for example, compounds based on Eu3+ ions. Complexes based on Eu3+ with 1,1,1-trifluoro4-phenyl-2,4-butanedione and acetic Eu(Cl)(Btfa)(CH3COO) (compound 1), butyric Eu(Btfa)2(CH3(CH2)3COO) (compound 2) acids were synthesized. The LEDs of the synthesized compounds were manufactured using a combined technique including the method of centrifugation and the method of thermal spraying in vacuum. The characteristics of the LEDs were measured by optical spectroscopy. To study the optical properties of the complexes, the powder was placed between two quartz substrates. Photoluminescence spectra were recorded using a SDL-1 spectrometer, an LED with a wavelength of 365 nm and a photoelectronic multiplier operating in linear mode. Electroluminescence spectra were obtained using the Ocean Optics Maya 2000 PRO spectrometer. A linear structure characteristic of Eu3+ ions was observed in the photoluminescence spectrum of the studied complexes. In the electroluminescence spectrum, radiation characteristic of Eu3+ ions is also observed, in addition to it, an additional wide band with a maximum at a wavelength of 390 nm and a half-height width of 61 nm is observed in the short-wavelength region. The operating voltage of the LED was 10 V. A characteristic “cold” white glow was observed for the studied LEDs. In the spectra of photos- and electroluminescence the following main transitions were found for the studied complexes: 5D0→ 7F0 (maxima at wavelengths λ1 = λ2 = 580 nm for compounds 1 and 2), 5D0 → 7F1 (split band, with maxima at wavelengths λ1 = 587 nm, λ2 = 593 nm, λ3 = 600 nm for the compound 1 and λ1 = 592 nm, λ2 = 599 nm for compound 2), 5D0 → 7F2 (split band, with maxima at wavelengths λ1 = 614 nm, λ2 = 619 nm, λ3 = 623 nm for compound 1 and λ1 = 614 nm, λ2 = 618 nm, λ3 = 620 nm for junction 2), 5D0 → 7F3 (split band, with maxima at wavelengths λ1 = 648 nm, λ2 = 652 nm, λ3 = 655 nm for junction 1 and λ1 = 652 nm, λ2 = 655 nm for compound 2). The wide band observed in the electroluminescence spectrum arises due to the contribution of the hole transport layer, due to the through flow of charge carriers through the active radiating layer, which leads to recombination in the PVK OLED layer. An analysis of the volt-ampere characteristics of the manufactured devices showed that they are characterized by two main conduction modes: the first corresponds to a limitation of the current by a spatial charge (0–7 V), the second is a limitation due to the processes of capture of charge carriers (7–23 V). The results of this work can be used in the production of industrial lighting.